Outward Direct Investment by Indonesian Firms: Motivation and Effects - Lecraw, Donald J. (Journal of International Business Studies, 1993)
As part of Indonesia's opening to the world economy, over the past several years Indonesian firms have begun to invest abroad. This study compares Indonesian firms that have invested abroad and those that have not and with Third World Multinationals and other MNEs. It found that the performance of Indonesian firms that invested abroad improved dramatically after their investment in terms of management expertise, exports, quality, and costs relative to their past performance and relative to the other firms in the sample. These results support a conclusion that Indonesian multinationals have gone abroad not only to exploit their ownership advantages but also to access and develop ownership advantages they did not previously possess.